Delayed presentation of a huge abdominopelvic mass during the COVID-19 pandemic. (October 2022) - Gurung, Rajan; Ali, Aishath Azna; Hayati, Firdaus; Rajakumar, Vishnu Vinodhan; Payus, Alvin Oliver; Wynn, Aye Aye; Azizan, Nornazirah; Ahmed Abdelhafez, Mohsen Mohamed; Abdullah, Bahiyah
Abstract: Background: Giant ovarian cysts are rare in developed countries due to advanced achievements in medical diagnostics. However, in the midst of the coronavirus disease 2019 (COVID-19) pandemic, patients with non-COVID-19-related illnesses tend to delay their health-seeking attention; thus, they had presented late. Case presentation: A 25-year-old single lady complained of a 3-month worsening abdominal pain and distention. She was initially well but neglected the symptoms due to the COVID-19 situation, yet came to our attention after she developed obstructive symptoms. A computed tomography (CT) scan of the abdomen revealed a huge cystic lesion from the pelvic area, which later was found to be from the right ovary upon urgent laparotomy exploration. The histopathological examination was consistent with mucinous cystadenoma of the ovary. Discussion: Acute non-COVID-19-related emergencies have decreased, as evidenced by reduced visits to the Emergency Department, and the number of abdominal CT scans. An emergency case like a huge abdominopelvic mass deserves an extensive radiologic examination as clinical assessment alone may not be adequate. Preoperative CT is superior to ultrasonography in getting the extent of the lesion, local infiltration, staging purpose, and surgical intervention. Pathology with a variety of spectrums such as mucinous neoplasm deserves to be investigated, evaluated, and resected even during the COVID-19 pandemic. Conclusion: A giant abdominopelvic cystic mass can present emergency havoc during the COVID-19 pandemic. Urgent surgical intervention is mandatory by using full protection and exercising extreme precaution, regardless of the preoperative screening to avoid unnecessary viral transmissions. Highlights: Acute abdomen cases have reduced in numbers during COVID-19 pandemic which can cause delay in diagnosis and management. Preoperative CT scan can determine the extent of the lesion, local infiltration, staging, and surgical intervention. During pandemic, urgent surgical intervention is mandatory by using full protection regardless of the preoperative screening to avoid unnecessary viral transmissions.